2002
DOI: 10.1046/j.1365-2672.2002.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and selection of vaginal Lactobacillus strains for the preparation of vaginal tablets

Abstract: Aims: To characterize and select Lactobacillus strains for properties that would make them a good alternative to the use of antibiotics to treat human vaginal infections. Methods and Results: Ten Lactobacillus strains belonging to four different Lactobacillus species were analysed for properties relating to mucosal colonization or microbial antagonism (adhesion to human epithelial cells, hydrogen peroxide production, antimicrobial activity towards Gardnerella vaginalis and Candida albicans and coaggregation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 28 publications
5
119
2
2
Order By: Relevance
“…Mean numbers of human urogenital lactobacilli adhering to uroepithelial cells ranged from 8 67 in studies by Boris et al (1998), and 23 48 in studies by Mastromarino et al (2002). Numbers of adhering lactobacilli in the present study were comparable.…”
Section: Discussionsupporting
confidence: 53%
“…Mean numbers of human urogenital lactobacilli adhering to uroepithelial cells ranged from 8 67 in studies by Boris et al (1998), and 23 48 in studies by Mastromarino et al (2002). Numbers of adhering lactobacilli in the present study were comparable.…”
Section: Discussionsupporting
confidence: 53%
“…During an 8-month study, Vallor et al (2) showed that, in contrast to L. crispatus and L. jensenii H 2 O 2 -producing isolates, strains that did not produce the antimicrobial substance were rapidly lost, a fact that supports the role of this production in sustained colonization. However, as demonstrated by diffusion assays, there is not always a direct correlation between the ability for H 2 O 2 production and the antagonistic activity of lactobacilli (24). In fact, the potential of H 2 O 2 production by Lactobacillus described here and in the literature has been demonstrated by in vitro assays and one must be cautious when extrapolating it to the in vivo environment.…”
Section: Discussionmentioning
confidence: 74%
“…Suspensions were observed by optic microscopy after Gram staining. 1 The score is based upon a scale described by Mastromarino et al (2002), from 0 for no aggregation to 3 for maximum aggregation. Table 12.…”
Section: S Cerevisiae Strainsmentioning
confidence: 99%